The Correlation Between Smart Board Learning Media (PAWITA) and Fourth-Grade Students’ Learning Attention in IPAS on Changes in the States of Matter at SDN Srengseng Sawah 15 - Eka Yuanda Putri; Dita Prihatna Wati (Journal of Educational Sciences, 2026)
Learning attention is an important component of effective elementary learning, particularly when students study concepts that are difficult to observe directly. In fourth-grade IPAS learning at SDN Srengseng Sawah 15, instruction was still dominated by teacher explanations and limited use of interactive media. This study aimed to examine the relationship between the use of Smart Board learning media (PAWITA) and students’ learning attention on changes in the states of matter. A quantitative correlational design was used with 31 fourth-grade students from Class IV B, which was selected through a random draw from two parallel classes, Class IV A and Class IV B. Data were collected using questionnaires measuring students’ perceptions of PAWITA and their learning attention, supported by documentation. Data analysis included descriptive statistics, the Kolmogorov-Smirnov normality test, linearity testing, and Pearson Product Moment correlation. The results showed that both variables were normally distributed and had a linear relationship. The Pearson Product Moment correlation analysis produced a coefficient of 0.616 with a significance value of < 0.001, indicating a strong and statistically significant positive relationship. Thus, the use of PAWITA was associated with higher levels of students’ learning attention. PAWITA can be considered an alternative visual and interactive instructional medium for supporting student engagement in learning about changes in the states of matter.